The law of the day and the passion for the night: The beautiful and good fight of Husserl and Jaspers (Phenomenology, Humanities and Sciences, 2025)
This paper aims to show the struggle with the power of the night in two great philosophers of the 20th century: Husserl and Jaspers. Like the great pessimists of thought, Husserl felt the presence of the shadow along his philosophical life. Furthermore, he was tormented by the possibility that life, even oriented towards a sunny goal, it could be finally a meeting with a pure nothingness. Husserl, having experienced the feeling of nullity of existence (Schopenhauer) was himself strong in the battle with a passive and fatalistic vision of the world and life. A similar struggle occurred with Jaspers, a philosopher of existence who actually explored the depth visualized by Husserl. There is a background of darkness that sustains us and without which we cannot reach ourselves through reflection. Even though he was faithful to the law of the day, Jaspers understood that the power of the night is greater than we imagine. “The powers that exercise their empire over us through their stimuli are incalculable.” Disconcerting conclusion: we can be attracted to that which destroys the general order and eliminates reason. When this actually happens, we fall into an uncontrollable whirlwind. We start to deny everything, including ourselves. How to understand this passion or temptation for the night? We will see that Husserl and Jaspers faced it in an essentially ethical way, thanks to a beautiful and good fight that kept them faithful to the law of the day.
Keywords: Keywords: Phenomenology, existence, ethics, night, meaning; Phenomenology; Existence; Ethics; Night; Meaning